KEMITRAAN BIDAN DAN DUKUN DALAM PENANGANAN IBU MELAHIRKAN - Ramli . (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2020)
The practice of childbirth labor in the village community is still carried out by traditional birth attendants, and there is a risk of the mother giving birth and the baby being born. The reality which then encourages the birth of a policy regarding the obligations of mothers giving birth must be helped by medical staff or midwives. In general, the purpose of this study is to explore how the partnership of midwives and traditional birth attendants in handling labor. The method used in this study is qualitative with an ethnometodological approach, with technical domain analysis. The results of the study explained that there was good cooperation between midwives and traditional birth attendants in handling labor. Collaboration between midwives and traditional birth attendants is made in an agreement to handle childbirth, and is always done with interpersonal communication between the two. In order not to create a negative impression between the midwife and the dukun, a partnership is needed through mutual agreement in the distribution of tasks, that the midwife helps labor while the dukun accompanies the mother, provides psychological support, and takes care of the mother and post-partum baby. In this study, problems can occur in pregnant women, midwives and traditional healers. Therefore it is necessary to have a good participation and cooperation between pregnant women/mothers with mothers, midwives and shamans